Usage of Inhaled Nitric Oxides in Cases of Eisenmenger Syndrome - Nenny Triastuti; Muhammad Perdana Airlangga; Muhammad Anas (Indonesian Journal of Medical Sciences and Public Health, 2020)
Eisenmenger Syndrome is congenital heart disease with pulmonary hypertension and shunting turning from right to left. The resistance of pulmonary vascular more than 7.5 mmHg/L/min. The right ventricle and pulmonary artery always enlarge. Physiological effects of inhaled nitric oxide therapy cause selective pulmonary vasodilation: Hypoxia alveoli causes reversible vasoconstriction, thereby increasing pulmonary wedge pressure. Inhaled nitric oxide can lower it. Moderate cardiac output and systematic arterial pressure are not affected; Selective in pulmonary because it is activated by hemoglobin; Selective vasodilation in the ventilated area, local hypoxia alveoli constricts the surrounding vascular tissue and redistributes blood flow to the ventilated lungs better and higher intraalveolar oxygen pressure. Inhaled nitric oxide enhances this mechanism by increasing blood flow through a well-ventilated lung; Bronchodilators; Pulmonary surfactant, The combination of high concentrations of inspired oxygen and high concentrations of Inhaled nitric oxide reduces the minimum surfactant surface tension.